Water-borne epoxy resin modified superfine sulphoaluminate cement-based fractured rock mass grouting plugging material
By using aqueous epoxy resin to modify ultrafine sulfur aluminate cement-based material, combined with nanosilia-silane coupling agent and anti-freeze-thaw agent, the problem of poor performance of composite grouting materials in coastal environments is solved, and high early strength, good freeze-thaw resistance and seawater erosion resistance are achieved.
Patent Information
- Application Number
- CN202411615673.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-25
AI Technical Summary
The existing composite grouting materials have problems such as poor freeze-thaw resistance, poor corrosion resistance, and low tensile strength in coastal corrosion environments, which are difficult to meet the engineering stability requirements of subsea tunnels and coastal rock slopes.
The ultrafine sulfur aluminate cement-based material is modified with aqueous epoxy resin, and the fluidity, freeze-thaw resistance and toughness of the material are improved by combining the nano-silia-silane coupling agent with the anti-freeze-thaw agent.
It significantly improves the early strength, flexural strength and permeability of the material, enhances its resistance to seawater erosion, and improves its service life in extreme environments.
Smart Images

Figure BDA0005132150440000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of underground engineering structure and rock mass grouting plugging and reinforcement materials, and in particular to a waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material. Background Art
[0002] In recent years, with the construction along the coast, the storm activities and sea level changes caused by climate warming, and the growth of coastal population, the engineering stability of submarine tunnels and coastal rock slopes has been severely challenged. The structure, physical and chemical properties of rock mass change under the long-term corrosion of seawater environment, resulting in broken rock mass with dense cracks and joints, which seriously affects the life of building structure engineering and the safety of personnel.
[0003] Grouting technology is a common method of repairing rock and soil, and is widely used in tunnels, slopes, and foundation projects. Grouting is the process of injecting a mixed slurry with filling and gelling properties into rock and soil, which diffuses in the soil or rock mass through penetration, filling, splitting, and extrusion, replacing the moisture and air in the soil particles or broken rock mass, and finally cementing into a whole structure, thereby improving the engineering geological conditions of the rock and soil mass or stratum.
[0004] At present, there are more and more studies on polymer-modified cement-based grouting materials. Polymers usually have the functions of water reduction, air entrainment, and water retention. Polymers have a great influence on the flow characteristics of cement-based grouting materials and can improve the working performance of polymer-modified cement-based materials. However, the effect of each polymer on the rheological properties of grouting materials is different. In addition, the hydration of the modified composite grouting material is affected by many factors such as the type, dosage, modification method, cement particle size, and aggregate composition of the polymer. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. The inventors found in their research that, so far, most composite grouting materials have poor freeze-thaw resistance, poor corrosion resistance, low tensile strength and other problems in coastal corrosion environments. Although relevant foreign scholars have conducted research on the modification of polymer concrete in acid-base environments, there are few studies on grouting materials. Existing polymer-modified cement-based grouting materials often encounter the following on-site problems because their performance is affected by many factors: 1. Ordinary cement-based materials cannot meet the corrosion resistance in coastal environments, and the slurry has poor stability, anti-scouring performance and durability, and the bonding surface between the slurry and the rock mass frequently cracks; 2. The particle size of ordinary cement-based materials is large, and it is difficult for the slurry to enter the fine cracks; 3. Most polymer-modified cement-based materials have poor freeze-thaw resistance and dry-wet resistance, and their deformation coordination is quite different from that of the rock mass, which can easily lead to failure of the bonding interface.
[0006] The purpose of the implementation method of this specification is to address the problems of poor grouting effect and poor treatment effect of broken rock mass in sea cliffs, and to provide grouting materials suitable for repairing coastal broken rock mass. A sulphoaluminate cement base material modified with water-based epoxy resin is used to meet the requirements of resistance to coastal corrosion environment and toughness repair.
[0007] In one aspect of the present invention, the present invention proposes a water-based epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material. According to an embodiment of the present invention, the water-based epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material comprises: a cement-based gel material, a water-based epoxy resin, a nano-silica-silane coupling agent and an admixture, and the cement-based gel material comprises sulphoaluminate cement. Sulphoaluminate cement has good flow characteristics and excellent mechanical properties under seawater conditions, and has the characteristics of rapid hardening and early strength, which can improve the early strength of the material.
[0008] According to an embodiment of the present invention, the above-mentioned water-based epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material may further include at least one of the following additional technical features:
[0009] It should be noted that in order to obtain better crack plugging effect, the cement material in the above-mentioned cementitious material should be ultrafine sulphoaluminate cement with small particle size.
[0010] According to an embodiment of the present invention, the strength grade of the sulphoaluminate cement is 42.5.
[0011] According to an embodiment of the present invention, the specific surface area of the sulphoaluminate cement is 875 m 2 / kg, D 50 17.3um, D 95 It is 41.8um.
[0012] According to an embodiment of the present invention, the water-based epoxy resin includes a water-based epoxy resin emulsion and a curing agent.
[0013] According to an embodiment of the present invention, the solid content of the waterborne epoxy resin is 40-60%.
[0014] According to an embodiment of the present invention, the mass ratio of the water-based epoxy resin emulsion to the curing agent is 1:1.3.
[0015] According to an embodiment of the present invention, the nano-silica-silane coupling agent comprises nano-silica particles, a silane coupling agent and a polymerization catalyst. According to an embodiment of the present invention, a silane coupling agent-grafted nano-silica composite particle is prepared by hydrothermal treatment of nano-silica, and the hydrolysis and condensation of the silane coupling agent is catalyzed by a polymerization catalyst to prepare a new interface coupling agent suitable for water-based epoxy resin modified composite grouting. It is used to significantly improve the bonding strength and reaction activity of the organic and inorganic interfaces in the modified composite grouting, and also avoid the adverse effects caused by the agglomeration of nano-silica and the hydrolysis of the silane coupling agent.
[0016] According to an embodiment of the present invention, the particle size of the nano-silicon dioxide particles is 20 nanometers. Nano-silicon dioxide of the above size can play a transmission effect between cement and large particles such as polymers, thereby improving the fluidity of the slurry.
[0017] According to an embodiment of the present invention, the silane coupling agent is 3-glycidyloxypropyltrimethoxysilane. The molecular formula of 3-glycidyloxypropyltrimethoxysilane is C9H 20 O5Si, CAS number is 2530-83-8. The above-mentioned silane coupling agent can better increase the grafting rate of nano-silicon dioxide, improve the degree of hydration reaction of the composite slurry, and enhance the improvement of the silane coupling agent-nano-silicon dioxide composite particles on the uniaxial compressive and tensile strength of the slurry.
[0018] According to an embodiment of the present invention, the polymerization catalyst is triethylenediamine TEDA catalyst. TEDA catalyst molecular formula: C6H 12 N2, CAS No. 280-57-9, the above polymerization catalyst can accelerate the condensation and hydrolysis process of nano-silica particles and silane coupling agent, thereby saving engineering time.
[0019] According to an embodiment of the present invention, the admixture includes a water reducing agent, an antifreeze-thaw agent and a retarder, so as to adjust the fluidity, freeze-thaw performance and setting time of the grouting material.
[0020] According to an embodiment of the present invention, the water reducing agent is a polycarboxylate water reducing agent. The polycarboxylate water reducing agent has good compatibility with waterborne epoxy resin, thereby improving fluidity.
[0021] According to an embodiment of the present invention, the solid content of the water reducing agent is 50%.
[0022] According to an embodiment of the present invention, the antifreeze-thaw agent is styrene-butadiene rubber. Styrene-butadiene rubber is used to improve the antifreeze-thaw property of the composite grouting material.
[0023] According to an embodiment of the present invention, the solid content of the antifreeze-thaw agent is 50%.
[0024] According to an embodiment of the present invention, the viscosity of the antifreeze-thaw agent is 50-300 mPa·s and the density is 1.04 g / cm 3 , average particle size D 50 It is 0.11um.
[0025] According to an embodiment of the present invention, the retarder is a boric acid retarder. The setting time of the grouting material is adjusted.
[0026] According to an embodiment of the present invention, the waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material includes the following components and mass fractions:
[0027] 65%-85% sulphoaluminate cement;
[0028] 3%-10% water-based epoxy resin;
[0029] 0%-2% nano-silicon dioxide;
[0030] 5%-10% silane coupling agent;
[0031] 0.4% water reducing agent;
[0032] 0%-20% antifreeze-thaw agent; and
[0033] 0%-3% retarder.
[0034] According to an embodiment of the present invention, the waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material includes the following components and mass fractions:
[0035] 70% sulphoaluminate cement;
[0036] 10% water-based epoxy resin;
[0037] 2% nano-silicon dioxide;
[0038] 10% silane coupling agent;
[0039] 0.4% water reducing agent;
[0040] 5% antifreeze-thaw agent; and
[0041] 2.6% retarder.
[0042] In another aspect of the present invention, the present invention provides a method for preparing a waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material. According to an embodiment of the present invention, the method comprises:
[0043] 1) performing a first mixing treatment on nano-silicon dioxide and deionized water to obtain a nano-silicon dioxide suspension;
[0044] 2) subjecting the nano-silica suspension and the pre-hydrolyzed silane coupling agent to a second mixing treatment to obtain a SiO2-KH560 solution;
[0045] 3) performing a third mixing treatment on the SiO 1-KH560 solution and TEDA to obtain silane coupling agent-nano silicon dioxide composite particles;
[0046] 4) performing a fourth mixing treatment on the silane coupling agent-nano silicon dioxide composite particles, the antifreeze-thaw agent and the aqueous epoxy resin solution to obtain an aqueous epoxy resin mixed solution;
[0047] 5) subjecting the water, the water reducing agent, the sulphoaluminate cement and the water-based epoxy resin mixed solution to a fifth mixing treatment to obtain a water-based epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material.
[0048] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:
[0049] According to an embodiment of the present invention, the mass ratio of the nano-silicon dioxide to deionized water is 1:19.
[0050] According to an embodiment of the present invention, the first mixing process includes a dispersion process and a hydrothermal process.
[0051] According to an embodiment of the present invention, the dispersion treatment is carried out in an emulsifier at a rotation speed of 5000 r / min for 30 minutes.
[0052] According to an embodiment of the present invention, the hydrothermal treatment is performed at 50° C. by continuous stirring with an electric stirrer for 6 hours.
[0053] According to an embodiment of the present invention, the third mixing process is performed at a temperature of 80° C. for 3 hours.
[0054] According to an embodiment of the present invention, the water-based epoxy resin solution is obtained by dissolving a water reducing agent, a retarder, a water-based epoxy resin emulsion and a curing agent in water and stirring the mixture, and the stirring time is not less than 1 minute.
[0055] According to an embodiment of the present invention, the fifth mixing process is performed in the following manner:
[0056] Add the mixed solution of water and water reducing agent into the mixer and mix with sulphoaluminate cement, stir slowly for 1.5 minutes and stir quickly for 1.5 minutes;
[0057] Adjust the mixer to slow stirring state, slowly add the modified water-based epoxy resin mixed solution, and stir slowly for 1.5 minutes.
[0058] In another aspect of the present invention, the present invention provides a method for preparing a waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material. According to an embodiment of the present invention, the method comprises:
[0059] Step 1: Mix nano-silica and deionized water in a ratio of 1:19, and disperse in an emulsifier at a speed of 5000r / min for 30min to prepare a uniform suspension. Stir continuously for 6h under hydrothermal conditions (50℃) with an electric stirrer; the silane coupling agent is pre-hydrolyzed 1h before the start of the test;
[0060] Step 2: Mixing the hydrothermally treated nano-silica suspension with the pre-hydrolyzed silane coupling agent to prepare SiO,-KH560;
[0061] Step 3: adding TEDA as a catalyst to the prepared SiO2-KH560 solution, the reaction temperature is 80°C, the reaction time is 3h, the reaction solution is centrifuged using a high-speed centrifuge, and the centrifuged particles are washed multiple times with anhydrous ethanol to obtain silane coupling agent-nanosilica composite particles;
[0062] Step 4: Weigh water according to a water-cement ratio of 0.8, weigh the water reducer and retarder according to the mass percentage, dissolve them in the water, and stir evenly: weigh the water-based epoxy resin emulsion and curing agent according to the mass percentage, mix them and stir evenly, and the stirring time shall not be less than 1 minute;
[0063] Step 5: Mix the prepared SiO2-KH560 particles, the antifreeze-thaw agent and the waterborne epoxy resin modified solution, stirring for 1 min to obtain a modified waterborne epoxy resin mixed solution;
[0064] Step 6: Add the mixed solution of water and water reducing agent into the mixer and mix with the ultrafine sulphoaluminate cement powder, stir slowly for 1.5 minutes and stir quickly for 1.5 minutes;
[0065] Step 7: Adjust the mixer to slow stirring state, slowly add the modified water-based epoxy resin mixed solution, and slowly stir for 1.5 minutes to obtain slurry, that is, water-based epoxy resin modified ultrafine sulphoaluminate cement-based grouting material.
[0066] According to an embodiment of the present invention, the prehydrolysis is carried out in the following manner:
[0067] Under the condition that the mass ratio of anhydrous ethanol and deionized water is 9:1, the silane coupling agent is added dropwise to mix, and the mass ratio of KH560 silane coupling agent, the prepared ethanol solution, and deionized water is 1:144:16, so that the pH value of the solution is stabilized at about 2. Then, the mixed solution is charged into a flask through a reflux device, and then heated to 90°C using a heating magnetic stirrer, and the solution is kept at 90°C for 20 minutes to obtain a pre-hydrolyzed silane coupling agent.
[0068] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0069] 1) The present invention provides a water-based epoxy resin modified sulphoaluminate cement-based coastal rock grouting material. The water-based epoxy resin used in the material uses water as a solvent and is basically pollution-free to the environment. The polymer film grid structure formed by the water-based epoxy resin cross-linking on the surface of cement particles can improve the toughness of the cement paste and increase the flexural strength of the modified composite cement paste; this polymer film grid structure can fill the pores of the cement hydration product to make the structure dense, and improve the anti-seepage performance of the water-based epoxy resin and microbially modified ultrafine cement-based waterproof plugging material: the water-based epoxy resin can reduce the drying shrinkage of cement;
[0070] 2) The present disclosure adopts ultrafine sulphoaluminate cement with fine particles, so that the composite material has excellent micro-crack permeability, is environmentally friendly and non-toxic, and has excellent seawater erosion resistance. At the same time, it has the characteristics of fast hardening and early strength, so the setting time of the water-based epoxy resin modified ultrafine sulphoaluminate cement-based grouting material can be shortened, the early strength is rapidly improved, and the seawater erosion resistance is enhanced;
[0071] 3) The present invention adopts a hydrothermally treated nano-silica-silane coupling agent to strengthen the organic and inorganic connection interfaces in the composite grouting material, which has a good modification effect on the compressive strength and splitting tensile strength of the grouting material stone body, can effectively improve the slurry retention rate of the cement grouting material under dynamic water scouring conditions, enhance the dynamic water scouring resistance of the cement-based grouting material, significantly improve the sulfate and sulfate-chloride corrosion resistance, and enable the grouting material to have a higher degree of hydration and a stronger resistance to salt solution corrosion.
[0072] 4) The present invention adopts styrene-butadiene rubber antifreeze-thaw agent to improve the mechanical properties of the composite grouting material under freeze-thaw cycles, improve its working characteristics, enhance the durability of the material in extreme low temperature environments, extend its working life, and save costs. DETAILED DESCRIPTION
[0073] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0074] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0075] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present disclosure. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0076] Aiming at the defects of existing engineering structures and rock mass grouting plugging reinforcement materials, the present invention provides a water-based epoxy resin modified ultrafine sulphoaluminate cement-based grouting material, which can control the setting time of the material by adjusting the mix ratio and is suitable for different plugging and reinforcement situations. At the same time, the material has the characteristics of strong seawater corrosion resistance, good fluidity, small late shrinkage, high early strength, and high bonding strength.
[0077] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0078] The ingredients and manufacturers used in the following invention are as follows:
[0079] Silane coupling agent: Model KH560, 3-glycidyloxypropyltrimethoxysilane, molecular formula: C9H20O5Si. KH-560 is an epoxy functional silane, produced by Dinghai Plastic Chemical Co., Ltd., Dongguan City, Guangdong Province;
[0080] Water reducer: The water reducer adopts polycarboxylate water reducer, which was purchased from a Shanghai Chemical Technology Co., Ltd., model CQJ-JSS02;
[0081] Antifreeze-thaw agent: Styrene-butadiene latex, with a water content of 0.85%, a tensile strength of 28 MPa, a combined styrene content of 25.35%, and a dry adhesive content of 77.8%, a product of PetroChina Lanzhou Petrochemical Company;
[0082] Retarder: The retarder is borax decahydrate, the molecular formula is Na2B4O7·10H2O, translucent colorless crystals or crystalline white powder, produced by Shandong Hanyue Chemical Co., Ltd.
[0083] Example 1
[0084] A waterborne epoxy resin modified ultrafine sulphoaluminate cement-based grouting material is composed of a gel material, a waterborne epoxy resin, a nano-silica-silane coupling agent and an admixture. The content of each component in the composite material is calculated by mass percentage as follows: ultrafine sulphoaluminate cement 70%. The content of the waterborne epoxy resin and the admixture components is calculated by their mass percentage of the gel material as follows: waterborne epoxy resin (emulsion + curing agent) 10%, nano-silica 2%, silane coupling agent 10%, water reducing agent 0.4%, antifreeze-thaw agent 5%, and retarder 2.6%.
[0085] Example 2
[0086] A waterborne epoxy resin modified ultrafine sulphoaluminate cement-based grouting material is composed of a gel material, a waterborne epoxy resin, a nano-silica-silane coupling agent and an admixture. The content of each component in the composite material is calculated by mass percentage as follows: ultrafine sulphoaluminate cement 70%. The content of the waterborne epoxy resin and the admixture components is calculated by their mass percentage of the gel material as follows: waterborne epoxy resin (emulsion + curing agent) 7%, nano-silica 2%, silane coupling agent 10%, water reducing agent 0.4%, antifreeze-thaw agent 8%, and retarder 2.6%.
[0087] Example 3
[0088] A water-based epoxy resin modified ultrafine sulphoaluminate cement-based grouting material is composed of a gel material, a water-based epoxy resin, a nano-silica-silane coupling agent and an admixture. The content of each component in the composite material is calculated as follows: ultrafine sulphoaluminate cement 70%. The content of the water-based epoxy resin and the admixture components is calculated as follows: water-based epoxy resin (emulsion + curing agent) 5%, nano-silica 2%, silane coupling agent 10%, water reducing agent 0.4%, antifreeze-thaw agent 10%, and retarder 2.6% based on their mass percentage in the gel material.
[0089] Example 4
[0090] A waterborne epoxy resin modified ultrafine sulphoaluminate cement-based grouting material is composed of a gel material, a waterborne epoxy resin and an admixture. The content of each component in the composite material is calculated by mass percentage as follows: ultrafine sulphoaluminate cement 70%. The content of the waterborne epoxy resin and the admixture components is calculated by their mass percentage of the gel material as follows: waterborne epoxy resin (emulsion + curing agent) 10%, water reducing agent 0.4%, antifreeze-thaw agent 10%, and retarder 2.6%.
[0091] Comparative Example 1
[0092] A waterborne epoxy resin modified ultrafine sulphoaluminate cement-based grouting material is composed of a gel material, a waterborne epoxy resin, a nano-silica-silane coupling agent and an admixture. The content of each component in the composite material is calculated by mass percentage as follows: ultrafine sulphoaluminate cement 97%. The content of the waterborne epoxy resin and the admixture components is calculated by their mass percentage in the gel material as follows: a water reducer 0.4% and a retarder 2.6%.
[0093] Performance Characterization of Leakage-Proofing and Reinforcement Materials in Examples
[0094] The prepared waterborne epoxy resin modified ultrafine sulphoaluminate cement-based grouting material was subjected to performance tests, and the results are as follows. Among them, the initial setting time and final setting time test methods are based on GB / T1346-2011 "Test Methods for Water Consumption, Setting Time and Stability of Cement Standard Consistency", the fluidity test method is based on GB50119-2013 "Technical Specifications for Application of Concrete Admixtures", and the flexural strength and compressive strength test methods are based on GB / T17671-1999 "Test Methods for Cement Mortar Strength". The material properties of Examples 1-4 and Comparative Example 1 are shown in Table 1.
[0095] Table 1 Performance of Examples 1-4 and Comparative Examples
[0096]
[0097] As can be seen from Table 1, the water-based epoxy resin modified ultrafine sulphoaluminate cement-based grouting material of the present invention has high early strength, and both 3d flexural strength and 3d compressive strength meet the strength requirements for inorganic waterproof plugging materials in the national standard GB23440-2009 (3d flexural strength ≥3MPa, 3d compressive strength ≥13MPa). The material has moderate late strength and moderate setting time, can meet the requirements of pumping construction, and has good flow properties, which is conducive to injection into fine cracks in the rock mass.
[0098] As shown in Table 1, Example 4 of the present invention has higher flexural strength and slightly improved compressive strength compared with Comparative Example 1. The waterborne epoxy resin used in the present invention can generate a polymer network structure in the cement paste to improve the toughness of the cement paste and the flexural strength of the composite grouting liquid.
[0099] As can be seen from Table 1, compared with Example 4, in Example 1 of the present invention, the nano-silica-silane coupling agent used can be grafted with the epoxy resin molecules and react with the hydrate to form a link between the epoxy resin and the cement gel, which further improves the flexural strength and compressive strength of the slurry compared to the single epoxy resin slurry.
[0100] As can be seen from Table 1, compared with Comparative Example 1, the antifreeze-thaw agent used in Example 1 of the present invention can effectively improve the antifreeze-thaw performance of the slurry modified with the water-based epoxy resin, which is beneficial to the rock grouting requirements in low-temperature areas and prolongs the service life of the material.
[0101] It is understood that, in the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", "other embodiments", or "first to Nth embodiments" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0102] The above description is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.
[0103] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
Claims
1. A water-based epoxy resin modified ultrafine sulphoaluminate cement-based broken rock grouting plugging material, characterized in that: include: Cement-based gel material, water-based epoxy resin, nano-silica-silane coupling agent and admixture, wherein the cement-based gel material comprises sulphoaluminate cement.
2. The water-based epoxy resin modified ultrafine sulphoaluminate cement-based broken rock grouting plugging material according to claim 1, characterized in that: The strength grade of the sulphoaluminate cement is 42.5; Optionally, the specific surface area of the sulphoaluminate cement is 875 m 2 / kg, D 50 17.3um, D 95 It is 41.8um.
3. The waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock grouting plugging material according to claim 1, characterized in that: The waterborne epoxy resin comprises a waterborne epoxy resin emulsion and a curing agent; Optionally, the solid content of the waterborne epoxy resin is 40 to 60%; Optionally, the mass ratio of the waterborne epoxy resin emulsion to the curing agent is 1:1.
3.
4. The waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock grouting plugging material according to claim 1, characterized in that: The nano-silica-silane coupling agent comprises nano-silica particles, a silane coupling agent and a polymerization catalyst; Optionally, the particle size of the nano-silicon dioxide particles is 20 nanometers; Optionally, the silane coupling agent is 3-glycidyloxypropyltrimethoxysilane; Optionally, the polymerization catalyst is a triethylenediamine TEDA catalyst.
5. The waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock grouting plugging material according to claim 1, characterized in that: The admixtures include water reducing agent, antifreeze-thaw agent and retarder; Optionally, the water reducer is a polycarboxylate water reducer; Optionally, the solid content of the water reducing agent is 50%; Optionally, the antifreeze-thaw agent is styrene-butadiene rubber; Optionally, the solid content of the antifreeze-thaw agent is 50%; Optionally, the antifreeze-thaw agent has a viscosity of 50-300 mPa·s and a density of 1.04 g / cm 3 , average particle size D 50 0.11um; Optionally, the retarder is a boric acid retarder.
6. The waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock grouting plugging material according to claim 1, characterized in that: include: 65%-85% sulphoaluminate cement; 3%-10% water-based epoxy resin; 0%-2% nano-silicon dioxide; 5%-10% silane coupling agent; 0.4% water reducing agent; 0%-20% antifreeze-thaw agent; and 0%-3% retarder.
7. The waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock grouting plugging material according to claim 6, characterized in that: include: 70% sulphoaluminate cement; 10% water-based epoxy resin; 2% nano-silicon dioxide; 10% silane coupling agent; 0.4% water reducing agent; 5% antifreeze-thaw agent; as well as 2.6% retarder.
8. A method for preparing a waterborne epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material, characterized in that: include: 1) performing a first mixing treatment on nano-silicon dioxide and deionized water to obtain a nano-silicon dioxide suspension; 2) subjecting the nano-silica suspension and the pre-hydrolyzed silane coupling agent to a second mixing treatment to obtain a SiO2-KH560 solution; 3) performing a third mixing treatment on the SiO 1-KH560 solution and TEDA to obtain silane coupling agent-nano silicon dioxide composite particles; 4) performing a fourth mixing treatment on the silane coupling agent-nano silicon dioxide composite particles, the antifreeze-thaw agent and the aqueous epoxy resin solution to obtain an aqueous epoxy resin mixed solution; 5) subjecting the water, the water reducing agent, the sulphoaluminate cement and the water-based epoxy resin mixed solution to a fifth mixing treatment to obtain a water-based epoxy resin modified ultrafine sulphoaluminate cement-based broken rock mass grouting plugging material.
9. The method according to claim 8, characterized in that The mass ratio of the nano-silicon dioxide to deionized water is 1:19; Optionally, the first mixing treatment includes a dispersion treatment and a hydrothermal treatment; Optionally, the dispersion treatment is carried out in an emulsifier at a speed of 5000 r / min for 30 min; Optionally, the hydrothermal treatment is carried out at 50° C. with continuous stirring by an electric stirrer for 6 h.
10. The method according to claim 8, characterized in that The third mixing treatment is carried out at a temperature of 80° C. for 3 hours; Optionally, the waterborne epoxy resin solution is obtained by dissolving a water reducing agent, a retarder, a waterborne epoxy resin emulsion and a curing agent in water and stirring the mixture, wherein the stirring time is not less than 1 minute; Optionally, the fifth mixing process is performed in the following manner: Add the mixed solution of water and water reducing agent into the mixer and mix with sulphoaluminate cement, stir slowly for 1.5 minutes and stir quickly for 1.5 minutes; Adjust the mixer to slow stirring state, slowly add the modified water-based epoxy resin mixed solution, and stir slowly for 1.5 minutes.
Citation Information
Cited By
Grouting material for deep cracked rock mass and preparation method thereof
CN122167117A
High-temperature two-component polymerized sulphoaluminate cement grouting material, its preparation and application
CN122586506A